FROM AWARENESS TO ADVOCACY: A CUSTOMER PATH 5A ANALYSIS OF MINISO CONSUMERS IN THE MARKETING 4.0 ERA - Nur Elisa Faizaty; Mar'atul Islamiyah; Mely Amalia Dwi Safira; Nur Hidayah (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2026)
The development of internet technology has significantly transformed consumer purchasing behavior and accelerated the growth of e-commerce platforms in Indonesia. As one of the largest e-commerce platforms, Shopee has become an important marketing channel for various brands, including Miniso. This study aims to analyze the influence of Shopee e-commerce on the Miniso brand in the era of Marketing 4.0 using the Customer Path 5A model, which consists of Aware, Appeal, Ask, Act, and Advocate. A quantitative approach was employed, and primary data were collected through questionnaires distributed via Google Forms to 90 Shopee users selected using purposive sampling. The findings indicate that consumer awareness of the Miniso brand was predominantly generated through offline stores (76.7%), while Instagram and Shopee played important roles in stimulating consumer interest and information-seeking behavior. Although digital platforms significantly influenced purchasing decisions, most respondents still preferred purchasing products through offline stores (53.3%). Furthermore, 72.2% of respondents recommended Miniso products to others, indicating a high level of customer advocacy. The study concludes that Shopee contributes positively to the customer journey by supporting information dissemination, consumer engagement, and brand advocacy. However, offline stores remain an essential touchpoint in influencing purchase decisions, highlighting the importance of an integrated omnichannel marketing strategy in the Marketing 4.0 era